Psychological distress in pregnancy and postpartum: a cross-sectional study of Babol pregnancy mental health registry - Shahnaz Barat; Azita Ghanbarpour; Seyyedeh Mahboubeh Mirtabar; Farzan Kheirkhah; Zahra Basirat; Hoda Shirafkan; Angela Hamidia; Faezeh Khorshidian; Davood Hosseini Talari; Zeynab Pahlavan; Sedigheh Esmaelzadeh; Zinatosadat Buzari; et al. (BMC, 2023)
Abstract Background Psychological distress (PD) is a significant issue during pregnancy and postpartum, adversely affecting both children and mothers. This study aims to determine PD's prevalence and risk factors in a large Iranian population sample during pregnancy and postpartum. Methods A cross-sectional study was conducted using data from the Babol Pregnancy Mental Health Registry (located in the north of Iran) between June 2020 and March 2021. A total of 2305 women were included, with 1639 during pregnancy and 666 during postpartum. Psychological distress was assessed using the Brief Symptoms Inventory (BSI-18), and data were analyzed using independent t-tests and multiple logistic regressions. Results The prevalence of psychological distress, defined by a cut-off score of BSI ≥ 13, was 19% during pregnancy and 15% during postpartum. Multivariate logistic analysis revealed that high-risk pregnancy was the leading risk factor for psychological distress during the antenatal period (β = 1.776, P < 0.001), as well as its three subscales: somatization (β = 1.355, P = 0.019), anxiety symptoms (β = 2.249, P < 0.001), and depressive symptoms (β = 1.381, P = 0.028). Additionally, women with a gestational age < 20 weeks had a higher risk of psychological distress (β = 1.344, P = 0.038) and the somatization subscale (β = 1.641, P < 0.001). During the postpartum period, women residing in urban areas were at higher risk of psychological distress (β = 1.949, P = 0.012), as well as two subscales: anxiety symptoms (β = 1.998, P = 0.012) and depressive symptoms (β = 1.949, P = 0.020). Conclusion The high prevalence of psychological distress emphasizes detecting and treating PD during pregnancy and postpartum, particularly in women with high-risk pregnancies. This study suggests that obstetricians and midwives should implement programs to identify women experiencing psychological distress during early pregnancy through postpartum visits.